Coitus and the causal cause of marriage - Sacher, Andrzej (Prawo Kanoniczne, 2023)
In the article entitled ‘Coitus and the causal cause of marriage’, the author presents an overview of the evolution of the teaching of the Catholic Church (canon law) on the role that the sexual conjugal act has played and continues to play in the formation of the marriage knot. He shows the influence that Roman, Celtic and Germanic law had on the Church's doctrine on this issue. The article also presents the discussions on the theological level and the current position of the Church on this matter as contained in the current code law.